IMPLEMENTATION OF THE COMMUNICATION COLLABORATION PROGRAM WITH THE COMMUNITY IN TUWUNG VILLAGE, BARRU DISTRICT - Dian Pratiwi; Marsuki; Arima (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal